SERANGAN HAMA KUMBANG (Oryctes rhinoceros L.) PADA TANAMAN KELAPA (Cocos nucifera L.) DI DESA MAPANGET KECAMATAN TALAWAAN KABUPATEN MINAHASA UTARA - Mei Lani Bandu; Dantje Tarore; Robert W Tairas (COCOS, 2018)
ABSTRACT  Coconut is an important plant for human life. The whole part of the coconut can be use start for not unlit the fruit. The production of coconut is very important for human along with the amount of production that reduced due to pest attack. Another factor that can inhibiti the growth of coconut is a pest attack.  This research is to know the attack of beetle pest O. rhinoceros on coconut plant in Mapanget, Talawaan sub district, Minahasa Utara regency which is two place is Mapanget an Lanbow garden, during three months start from october to december 2017.  This research is use survey method or by direct observation.  The result of this research show percentage of pest attack on Mapanget garden by O. rhinoceros in firsh and two second egual to 60,45% and 60,76% and at the third egual 61,17%.  Percentage of pest attack on Lanbow garden by O. rhinoceros in the firsh and second month egual to 18,38% and 19,15% and then at the third month 20,19%.  Keywords: Percentage, O. rhinoceros, Coconut